A Novel and Efficient Reader-to-Reader and Tag-to-Tag Anti-Collision Protocol. Issue 3 (4th May 2021) - Kumar, Adarsh; Aggarwal, Alok; Gopal, Krishna
ABSTRACT: Radio Frequency IDentification (RFID) is one of the prominent wireless technologies for implementing a complete smart environment and is preferred over magnetic tapes, bar codes and smart cards due to its low cost and high speed. RFID networks provide identification, location tracking and record management and consist of tags, readers and backend storage devices. In these networks, it is very common to see tag-to-tag or reader-to-reader collisions. For avoiding these collisions and hence to improve the overall system performance many probabilistic and deterministic anti-collision protocols have been proposed, but the majority of these protocols were found to be inefficient in channel distribution. In this work, based on simulation annealing, a novel and efficient reader-to-reader and tag-to-tag anti-collision protocol is proposed by uniformly distributing the available channels among different readers, which reduces reader-to-reader collisions to zero. For a better performance tag state parameters have been preferred over fixed scheduling. Improvement of tag identification ratio from 1% to 12.5%, successful interrogation cycles by up to 25% for a maximum of 1000 readers and reduction in the number of cycles required for interrogation by a minimum of 13.3% and a maximum of 25.5% and reader-to-reader collisions up to 24% for 100 K tags make the proposed protocol much suited to a heavily loaded network. Compared to other contemporary protocols performance gain in the range of 2% to 30% has been observed for the total number of sent/received packets, delay, number of collisions, idle cycles and time cycles.